Analisis Fraud Diamond, dan Komite Audit dalam Mendeteksi Fraudulent Financial Statement : (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Deswytha Maharany Riduan; Marieta Ariani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This research aims to test and provide evidence about whether Financial stability, Ineffective Monitoring, Change in Auditor, Change in Directors, Audit Committee have an influence on Fraudulent Financial Statements. This research uses secondary data obtained from annual reports of banking sector service companies listed on the Indonesia Stock Exchange (BEI) obtained from the official IDX website and the official websites of related companies in the period 2021 to 2023. The sampling method in this research is purposive sampling. The test carried out in this research is a multiple linear regression test processed using SPSS 22. The results of the research show that Financial Stability has a positive effect on Fraudulent Financial Statements, Ineffective Monitoring and Change in Auditors, have no effect on Fraudulent Financial Statements and for the Audit Committee it has a negative effect on Fraudulent Financial Statements.